Changes in Symptom Burden in Dialysis Patients Assessed Using a Symptom-Reporting Questionnaire in Clinic. Issue 1 (January 2020) - Moskovitch, Jeremy T.; Mount, Peter F.; Davies, Matthew R. P.
Introduction: To determine the prevalence, severity, and change in symptoms experienced by dialysis patients following the introduction of use of a symptom-reporting questionnaire in nephrology clinic. Methods: This is an observational study of 160 prevalent dialysis patients. Palliative care Outcome Scale symptom (POS-renal) questionnaires modified for patients with end-stage kidney disease were completed at baseline and follow-up (median 3 months), with results available to nephrologists at clinic appointments. Findings: The baseline prevalence of individual symptoms ranged from 15% to 66%. The most common symptoms were lack of energy (66%) and poor mobility (58%). The median number of symptoms was 7/17 (interquartile range [IQR]: 4-10). Forty-nine percent of patients rated at least 1 symptom as severe or overwhelming. At follow-up, the median number of symptoms experienced was unchanged at 7/17 (IQR: 3-10). However, there was considerable flux in symptom severity. On average, individual symptoms that were present at baseline improved in 56% of patients and worsened in 18%; only 26% had stable symptom severity. Individual symptoms newly occurred in 8% to 20% of patients between time points, with 77% of patients experiencing at least 1 new symptom. The percent of patients rating at least 1 symptom as severe or overwhelming was reduced from 49% to 39% ( P = .040). Conclusions: Use of the POS-renal questionnaire identified a high symptom burden. The presence and severity of symptoms changed dramatically over a short follow-up period, highlighting the need for regular surveillance of symptoms in the dialysis population. Routine use of a symptom questionnaire in clinic may be useful for the identification and management of symptoms in dialysis patients.